Leveraging social media for eco-education: home gardening for climate resilience and food security - Frank Yeboah Adusei; Yaw Asamoah Akowuah; Frank Kwekucher Ackah; Loy Van Crowder; Edmond Yeboah Nyamah; Mary Michael Lipford Zahed (Academia Environmental Sciences and Sustainability)
This study explores the integration of social media as a tool to promote environmental education and sustainability through home gardening initiatives in Ghana. The focus is on leveraging social media platforms like Facebook, specifically the Home Gardening, Ghana (HGG) initiative, to address challenges related to food security, urbanization, and climate resilience. HGG has deep cultural and environmental roots, providing significant contributions to food security and biodiversity conservation. It has created an online community of over 300,000 members, offering practical training and fostering community engagement. Using a qualitative research approach, this study evaluates HGG’s impact on food security, community resilience, and environmental conservation, based on responses from 100 participants. The findings highlight the initiative’s role in enhancing household food security, reducing food costs, and promoting sustainable practices. Challenges such as limited access to resources and the digital divide in rural areas are also identified, along with the significant role of women in driving home gardening efforts. Social media is shown to be a powerful platform for knowledge dissemination, peer support, and fostering collective action for environmental education. This research underscores the transformative potential of digital communication in addressing climate change and urban food insecurity in Ghana.